Efficient resource provisioning using traffic balancing in multidomain optical networks. (13th October 2016) - Batham, Deepak; Yadav, Dharmendra Singh; Prakash, Shashi
Summary: In multidomain optical networks (MDONs) the emerging multimedia, multivendor applications–based scheduled traffic (ST) is periodic and repeated day by day. The traffic is heavy during the working hours and slack during the non‐office hours. This results in the scarcity of network resources during the working hours, leading to the increased blocking of requests, even though there remains relatively large underused capacity during the non‐office hours. To use the network resources uniformly and efficiently, the demands may be slided within or shifted along the time zones/windows. In this paper, we first propose a heuristic algorithm, time‐aware routing and wavelength assignment (TA‐RWA), which allocates resources without traffic balancing (TB) for the ST in MDON. Time‐aware routing and wavelength assignment policy is then used as a benchmark for comparison with the 3 different TB solutions (named as P1‐TB, P2‐TB, and P3‐TB), in which the network load is redistributed by rescheduling the intradomain and interdomain demands. We performed extensive simulation experiments in MATLAB environment and compared the proposed policies with the existing ordering policies. From the results, it can be inferred that the proposed TB policies outperform the TA‐RWA, and the existing strategies of the blocking probability, resource utilization ratio (RUR), and percentage of intradomain and interdomain connections established. The best performance is achieved using P3‐TB strategy, in which requests are slided within, and shifted, along different time windows. The strategy shows about 70% reduction in the percentage blocking probability with respect to the TA‐RWA and the existing strategies. Abstract : In multidomain optical networks (MDONs) the emerging multimedia, multivendor applications based scheduled traffic is periodic and repeated day‐by‐day. The traffic is heavy during the working hours and slack during the non‐office hours. We proposed the resource provisioning by incorporating traffic balancing on the basis of service level agreement between the service provider and customer. The traffic may be slided within or shifted beyond the time zones to reduce the traffic unevenness and use the network resources efficiently.